STUDY OF SUSTAINABLE PUBLIC SPACE IMPLEMENTATION IN WONOREJO SEED GARDEN, SURABAYA - Firdaus, Annisa Izzati; Utomo, Heru Prasetiyo (Border: Jurnal Arsitektur, 2022)
Public space is the character and identity of a city. Public Space is a facility that is able to accommodate the interaction of diverse and dynamic urban communities, such as the Wonorejo Nursery which is located in the city of Surabaya. With climate and global warming issues becoming more and more worrisome, sustainable public spaces are very important because they can have a positive impact on urban life as a whole. Therefore, this study aims to examine the principles of sustainable public space that are applied to parks in the city of Surabaya. In this study, the Wonorejo Nursery was chosen as a case study because the Wonorejo Nursery is the largest and busiest park in the East Surabaya area. So the presence of the Wonorejo Nursery has significant implications for the lives of East Surabaya residents. With this significance, the study of the implementation of sustainable public space in this park can provide an overview of the impact of park development on the surrounding environment in terms of sustainability issues. This research is a qualitative research, with a descriptive-analytic type. The results of the analysis show that the Wonorejo nursery implements several elements of sustainable public space, but in some facilities it still requires improvement and development so that it can function optimally.